Commodity frontiers expand more slowly into tropical forests where forest smallholders are present - Marie Pratzer; Patrick Meyfroidt; Maria Vallejos; Tobias Kuemmerle (Proceedings of the National Academy of Sciences, 2026)
The expansion of commodity agriculture into tropical forests leads to major social–ecological impacts. Yet little is known about where and how the capitalized actors driving this expansion interact with smallholders, particularly where smallholders live inside the forest. Two alternative outcomes of their interactions on deforestation are plausible: accelerated deforestation as all actors compete for land (i.e., land rush hypothesis) or, alternatively, slower deforestation as actors hinder each other’s expansion (i.e., competition hypothesis). We test these hypotheses for two global deforestation hotspots: the Dry Chaco and the Chiquitano Forests (together nearly 1 million km 2 ), using a land-systems representation that captures spatially overlapping land-use actors. We integrate satellite-based forest-loss time series with an independent reconstruction of land-system change from 2000 to 2023 in a Bayesian regression framework. This reveals three key findings: First, capitalized agriculture has expanded mainly over areas used by forest-dependent smallholders and Indigenous communities, indicating strongly intensifying land competition. Second, where forest-dwelling smallholders persist, their presence can mitigate deforestation pressure from expanding commodity frontiers. Third, the presence of either forest-dwelling smallholders or conservation areas maintains forest cover, but their combined presence does not amplify the protection effect. Overall, our findings show that interactions between agribusinesses and smallholders are key factors that shape the social–ecological outcomes of frontier expansion in the tropics. Accounting for land-system overlaps in research and policymaking on frontiers can therefore improve efforts to safeguard forests while supporting traditional livelihoods, especially in contested, rapidly changing landscapes.